2014
DOI: 10.1515/bmc-2014-0032
|View full text |Cite
|
Sign up to set email alerts
|

Latrophilins updated

Abstract: Latrophilins (LPHN) are part of a yet unexplored family of receptors comprising three isoforms, LPHN1-3, and belonging to a unique branch of G protein-coupled receptors (GPCR) named adhesion GPCR (aGPCR). LPHN are considered to be prototypical models for the study of aGPCR as they are one of the most evolutionary conserved members. Previously described as the target for a potent neurotoxin from the black widow spider venom, LPHN are now being studied under a whole new perspective. Indeed, recent advances have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 123 publications
(211 reference statements)
1
27
0
Order By: Relevance
“…The latrophilins/ADGRL1-3 and BAIs/ADGRB1-3 appear to be critical for synapse formation and strengthening. ADGRL1-3 receptors are found in both pre-and post-synaptic compartments (103). Human studies have linked ADGRL3 to attention deficit hyperactivity disorder (ADHD) (104; 105) and animal studies have supported this finding.…”
Section: Adhesion Gpcrs In Nervous System Function and Diseasementioning
confidence: 99%
“…The latrophilins/ADGRL1-3 and BAIs/ADGRB1-3 appear to be critical for synapse formation and strengthening. ADGRL1-3 receptors are found in both pre-and post-synaptic compartments (103). Human studies have linked ADGRL3 to attention deficit hyperactivity disorder (ADHD) (104; 105) and animal studies have supported this finding.…”
Section: Adhesion Gpcrs In Nervous System Function and Diseasementioning
confidence: 99%
“…Large‐scale RNAi screening has identified 25 GPCRs that could potentially be novel insecticide targets based on the fact that knockdown of these GPCRs results in more than 30% mortality in T. castaneum . One of the identified GPCRs is latrophilin ( lph ), which was previously described as the target of a potent α‐latrotoxin from black widow spider venom . We discovered that Tclph mRNA is highly expressed in the central nervous system (CNS) of T. castaneum .…”
Section: Introductionmentioning
confidence: 99%
“…38,44 One of the identified GPCRs is latrophilin (lph), which was previously described as the target of a potent -latrotoxin from black widow spider venom. 45 We discovered that Tclph mRNA is highly expressed in the central nervous system (CNS) of T. castaneum. 46 Additionally, our latest studies further showed that the transcripts of Tclph are dramatically induced by dichlorvos (an organophosphorus insecticide) and carbofuran (a carbamate insecticide), two key anticholinesterase insecticides that kill insects through overstimulation of the nervous system; knockdown of Tclph also significantly enhanced the susceptibility of the larvae to these two insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…). Possible phosphorylation of LPHN1 has been previously mentioned in several reviews, including a very comprehensive literature analysis, but, to our knowledge, never experimentally addressed (except using MS2‐based predictions, see below). However, phosphorylation of GPCRs is very important for their functions and, therefore, deserves an in‐depth investigation.…”
Section: Discussionmentioning
confidence: 98%